Analysis of Household Air Pollution and Its Association with Acute Respiratory Infection Incidence in Women Living in Rural Agro-Industrial Areas - Rahmah Juliani Siregar; Willhelmina Wahara; Nour Sriyanah; Maryam Latifah Harahap; Eko Mulyadi (PT Inovasi Pratama Internasional, 2026)
Introduction: Household air pollution (HAP) from solid fuel combustion remains a leading environmental health threat, yet its specific impact on women in rural agro-industrial areas, where agricultural residues are commonly used as cooking fuel, is poorly documented. This study aimed to measure HAP levels and determine their association with acute respiratory infection (ARI) incidence among women in these settings. Method: A cross-sectional study was conducted among 250 women from three rural villages in an agro-industrial region. Indoor PM2.5 and carbon monoxide (CO) concentrations were monitored over 24 hours using portable air samplers. Data on ARI symptoms (cough, fever, and difficulty breathing) and household fuel use were collected via validated questionnaires. Multivariate logistic regression was used to assess associations. Results: Mean 24-hour PM2.5 and CO levels were 285 µg/m³ and 7.2 ppm, respectively, both far exceeding WHO safety thresholds. Biomass fuel use dominated (78%), primarily agricultural waste. ARI prevalence reached 42%. After adjusting for confounders, elevated PM2.5 was significantly associated with ARI (AOR=2.8; 95% CI: 1.6–4.9), alongside biomass fuel use and prolonged cooking time. Discussion: The strong dose-response relationship suggests that chronic exposure to high particulate matter from agricultural residues directly compromises respiratory defenses. The synergistic effect of indoor smoke and poor ventilation likely exacerbates infection risk, highlighting a overlooked occupational-exposure pattern in agrarian communities. Conclusion: Urgent interventions particularly cleaner cookstove programs and kitchen design improvements are essential to reduce the substantial ARI burden among this vulnerable population.